Sistem Pendukung Keputusan Untuk Menentukan Supplier Jeruk Peras Terbaik Menggunakan Metode TOPSIS Berbasis Web Pada Skys Orange - Ihsan Harviansah; Teti Desyani (CV. Shofanah Media Berkah, 2026)
An objective and efficient supplier selection process is vital for managing squeezed-orange procurement at SKYS ORANGE. Previously, supplier evaluation was conducted manually, which often led to subjective judgments, longer processing time, and potential calculation errors when comparing numerous alternatives. This research aims to design and implement a web-based Decision Support System (DSS) by applying the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to generate transparent and accountable supplier rankings. The evaluation criteria include price, product quality, and supplier distance, with weights that can be adjusted according to managerial priorities. The computational stages involve constructing and normalizing the decision matrix, applying weighted values, determining positive and negative ideal solutions, calculating separation distances, and computing preference scores to obtain the final ranking results. A relational database is utilized to facilitate structured data entry, criteria weight configuration, and systematic recording of calculation logs for audit purposes. System validation was carried out through functional testing scenarios and preliminary user trials to evaluate feature performance and usability. The findings demonstrate that the developed system enhances objectivity, operational efficiency, and consistency in supplier assessment, while also allowing the procurement team to clearly trace the basis of each generated decision.